The role of circulating free nucleic acids on Alzheimer's Disease (Research, Society and Development, 2025)
The study aims to understand the multifactorial foundation that could contribute to a deeper understanding of this issue. Alzheimer's disease is a neurodegenerative disorder primarily caused by idiopathic factors. However, it is almost universally agreed that genetic factors and the deposition of beta-amyloid plaques in senile plaques, along with tau protein, negatively influence its progression. Additionally, more recent evidence suggests a greater plausibility of factors that have been less discussed until now, such as circulating free nucleic acids. Oxidative stress caused by a neuroinflammatory process is triggered by the recognition of these substances in their circulating form, resulting from tissue damage caused by free radicals, which appear as damage-associated molecular patterns (DAMPs). This occurs through a positive feedback process involving the activation of the innate immune system, including microglia, astrocytes, blood-brain barrier proteins, cytokines, the complement system, and transmembrane receptors. In an insufficient attempt to clear the nervous system of DAMPs, this response ultimately induces and sustains a chronic immune cascade. However, despite the strong relationship between these factors and the development of Alzheimer's disease, the topic remains recent and clinically underexplored. Therefore, further theoretical exploration and the development of more laboratory tests are necessary to substantiate the theoretical framework discussed in the current literature on this subject.